2020
DOI: 10.1002/jemt.23568
|View full text |Cite
|
Sign up to set email alerts
|

Sloths (Bradypus variegatus) as a polygastric mammal

Abstract: Fermentative herbivorous animals have peculiar conformations of the digestive system. It is known that B. variegatus obtained the capacity for evolutionary adaptation, due to their ecology and eating habits. However, despite the literature on feeding management for this species, there is a lack of published information regarding its gastric morphology, and such information would support a better understanding on the diet and digestion of these individuals. We found seven gastric compartments, which histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The esophageal rupture in its cervical portion, observed in one of the corpses, is probably related to an attempt to insert an esophageal catheter, as this fact was described in the animal's medical record, but this alteration may also be due to a bad disposition of the oral contrast or a morphological alteration in the esophagus [28]. The location of the esophagus corroborates the studies that identified the structure and its location in dissected samples of B. variegatus [29].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The esophageal rupture in its cervical portion, observed in one of the corpses, is probably related to an attempt to insert an esophageal catheter, as this fact was described in the animal's medical record, but this alteration may also be due to a bad disposition of the oral contrast or a morphological alteration in the esophagus [28]. The location of the esophagus corroborates the studies that identified the structure and its location in dissected samples of B. variegatus [29].…”
Section: Discussionsupporting
confidence: 73%
“…In B. variegatus, the stomach is highly complex, presenting four gastric chambers that are subdivided into seven compartments [29,30]. In the exam performed in this study, contrast highlighted only part of these chambers, probably due to the small volume of contrast administered and also to the absence of gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 65%
“…These animals have developed anatomically and physiologically in line with their eating habits, with a digestive system that has ruminal characteristics and molarized teeth that are constantly worn down in the act of grinding vegetable matter (Azarias et al., 2006; Mesquita et al., 2021). The oral health of animals is closely related to the maintenance of nutritional health, reproductive capacity, longevity and quality of life (Magalhães et al., 2019).…”
Section: Introductionmentioning
confidence: 99%